Educational Game “Algo Fun” to Improve Learning Outcomes in Algorithm Material in Informatics Subject Class VII - Della Okvrika Widyani; Octaviany Widyaningsih (Universitas Pendidikan Ganesha, 2025)
Many students have difficulty in understanding the concept of Algorithms in Informatics, which leads to low learning outcomes. Conventional learning methods that are not interactive also worsen student engagement in the learning process. This study aims to evaluate the effectiveness and feasibility of the educational game “Algo Fun” in improving students' higher order thinking skills on Algorithm material. This type of research is research and development (R&D) with the ADDIE development model. The research subjects consisted of 26 students of class VII A as the experimental group and 30 students of class VII B as the control group. Data were collected using observation, interview, documentation, questionnaire, and test methods. While the instruments used were questionnaire sheets in the form of Likert scales and test sheets. The data analysis technique used quantitative descriptive analysis and N-Gain calculation. The validation results showed that the media was very valid, and the trial results showed a significant increase in the experimental class post-test score compared to the control class. The conclusion of this study is that “Algo Fun” is very valid, feasible, and effective in improving student learning outcomes related to the concept of Algorithm. This study implies the importance of integrating interactive media in learning Informatics to foster engagement and in-depth understanding of concepts.